Dental Status Of The Oral Cavity In Industrial Enterprises "Textile Finance Khorezm" Workers, Development Of Prevention Ways (Eurasian Medical Research Periodical, 2023)
The high prevalence and intensity, first of all, of caries and periodontal diseases among trainee workers of industrial enterprises are known, as well as the great need among them for dental treatment and prosthetics [Kabirova M.F., Usmanova I.N., 2009; Leonova L.E., Kamenskikh M.V., 2011; Leskov A.S., 2012; Saradzhev, V.V., 2005; Khavkina E.Yu., Olesov E.E., Maksyukov S.Yu., Makeev A.A., Rogatnev V.P., Magamedkhanov Yu.M., Kuznetsov A.V., Kolyabina Yu.V., 2011] . At the same time, the majority of workers with extensive experience have general somatic diseases, and there remains low motivation to maintain dental health and adequate oral hygiene [Dubinina L.M., 2008; Kolyabina Yu.V., 2010; Kononenko V.I., Bronshtein D.A., Olesov E.E., Khlutkov E.S., Yarilkina S.P., Kishko E.V., Zharov A.V., Rudakov V.A., 2012; Olesova V.N., Sorokoumov G.L., Balkarov A.O., Zakariev Z.Z., Pavlova N.A., Musheev I.U., 2007] Large industrial enterprises have departmental medical services, including dental, and sanatoriums for the medical rehabilitation of their employees